Percepção da voz em professoras: narrativas de vida entre os espaços do trabalho e do coro cênico - Blanco, Eliane Selma do Valle [UNIFESP] (2017)
This research tries to understand the use and perceptions of the voice of teachers who participate in the scenic choir “Céu da Boca” and covered the objectives: to investigate the perception of the use of voice as a tool of work and as an instrument of expression of art, in a choir of teachers of the Early Childhood Education in Santos; understand the relationship that a teacher establishes between the spoken voice (professional use) and the voice sung (amateur use); identifying the quality of vocal health, to promote strategies aimed at prevention and care at the individual and collective levels. It is a qualitative research, in which the ethnographic method was used, with the production and analysis of field diaries and participant observation. The elaboration of five life history narratives with the participating teachers and the conductor of the choir was used as a methodological resource in the production of data and approximation between subjects, who in this case are the researcher and the participants of the research. These narratives and the contents of the field diary were analyzed from the perspective of some issues, such as: the use of voice in art and the use of voice in the profession; the influence of working time on vocal use and / or overuse; the influence of work organization on the use of the voice of those teachers; how those professionals take care of vocal health, in relation to their lifestyle, the different ways of managing time and their different roles: woman, mother, teacher, singer. In the final considerations, it was possible to observe that Arts, music, participation in a singing group (choir) can be an efficient strategy not only for the promotion of vocal health but also for the choice of lifestyles in which those women take care of themselves. The second point is that there is little provision of prevention programmes and vocal health promotion for teachers, both in terms of those offered by the occupational health system and those offered by the institutions where teachers work.